Perilaku Return Saham Berbasis ESG Sebelum dan Saat Krisis: Pendekatan Model Fama-French Tiga Faktor - Bilqis Hermawan; Meinanda Kurniawan (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze the return behavior of Environmental, Social, and Governance (ESG)-based stocks in the Indonesian capital market using the Fama-French three-factor model during the pre-crisis period and during the COVID-19 pandemic crisis. The research sample includes individual stocks that were constituents of the SRI-KEHATI Index during the period from May 2017 to May 2023, with data processed on a weekly basis. The analysis method used is pooled ordinary least squares (OLS) regression with the application of robust standard errors to overcome potential violations of classical assumptions. The results show that market factors have a positive and significant effect on ESG-based stock excess returns in both periods, although their sensitivity decreases during the crisis. Company size factors were significant before the crisis but lost their significance during the crisis period, reflecting changes in investor risk preferences. Conversely, the company value factor shows a consistent and increasingly strong role during the crisis period. In addition, abnormal returns on ESG-based stocks are only found in the pre-crisis period. These findings indicate that the mechanism of ESG-based stock return formation is influenced by market conditions and emphasize the importance of adjusting ESG investment strategies in line with the economic cycle.